2009
DOI: 10.3810/psm.2009.12.1739
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Local Vibration Therapy on Ankle Sprain and Hamstring Strain Injuries

Abstract: Segmental BMS therapy using the Swisswing device appears to have significant acute benefits for improving flexibility and reducing perceived stiffness in healthy adults with ankle or hamstring injury. Future research is needed to determine the duration of these effects and if repeated periods of segmental BMS therapy aid in long-term injury recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…As noted by previous studies, SVT can be applied more frequently than traditional sound wave and ESWT treatments 3,5,7 . Cacchio et al reported on their results of a Level I study on "shockwave" for proximal hamstring tendinopathy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As noted by previous studies, SVT can be applied more frequently than traditional sound wave and ESWT treatments 3,5,7 . Cacchio et al reported on their results of a Level I study on "shockwave" for proximal hamstring tendinopathy.…”
Section: Discussionmentioning
confidence: 95%
“…This device is applied to the affected area for 2500 pulses at 4.0 Bar and 35 Hz ( These two types of treatments are able to be combined in one device. This pressure wave treatment typically takes four minutes, which corresponds with current research recommendations 3,4,7 . Activities as tolerated are permitted after the treatments though generally running and jumping are not allowed for 3-6 weeks.…”
Section: Proposed Treatment Protocol For Calf Strainsmentioning
confidence: 99%
“…Peer et al 73 reported that 10 minutes of intermittent direct VT (20 Hz) was more effective in treating hamstring and ankle sprains than 20 minutes of controlled therapy using ice, compression and elevation. The authors reported that flexibility of the hamstring and tricep surae muscle groups increased and perceived stiffness decreased.…”
Section: Injury Rehabilitationmentioning
confidence: 98%
“…Each muscle group was stimulated for 2 minutes at 20 hertz, as recommended by the manufacturer and previous publications [18,20]. Lower body muscle groups were stimulated either seated or standing and included: gluteals -standing with buttocks resting on drum; hamstrings -standing with hamstring draped over drum; gastrocnemius-seated with belly of the calf draped over the drum; hip adductors-standing with side of thigh resting on the drum; hip flexorsstanding with front of the hip touching the drum.…”
Section: Segmental Vibration Therapymentioning
confidence: 99%